The role of human resource management in increasing employee creativity and productivity, a case study at Dewi Rengganis Batik House - Cahya Pratiwi; Malika Liana Zaharani; Holipatun Nisa; Husni Mubarak; Saiful Islam; Yeni Kartikawati (Economic: Journal Economic and Business, 2026)
Human Resource Management (HRM) is a series of activities that include planning, organizing, developing, motivating, and supervising human resources in an organization to achieve goals effectively and efficiently. This study aims to examine the role of human resource management in increasing employee creativity and productivity at Rumah Batik Dewi Rengganis. Increasingly fierce competition in the batik industry requires business actors to continue to innovate and produce high-quality products. In this context, effective human resource management is a key factor in organizational success. The research method used is a case study with a qualitative approach, which is carried out through data collection techniques such as interviews, observation, and documentation. The results of the study indicate that human resource management which includes skills training, increasing work motivation, and implementing open and effective communication has a significant contribution to increasing employee creativity in producing innovative and diverse batik designs. In addition, the effectiveness of employee management also has a positive impact on increasing production productivity at Rumah Batik Dewi Rengganis.